UTILIZATION OF WATER HYACINTH AS ACQUIRED BIOGAS, LIQUID FERTILIZER AND CONTROL ITS SPREAD - Agus Hadiyarto; Alfiyanti Alfiyanti; Deo Reynaldo Alwi; Noor Hanifah Angga Putra (Diponegoro University, 2019)
Calombo hamlet, Semarang Regency has a population of 1,125 peoples, live at coast side of Rawapening Lake. Much of the water hyacinth covered Rawapening Lake thus decreasing fisheries production. The growth of water hyacinth has been decreased by using it as craft materials and compost, but not optimally. Need other efforts to reduce the density for example convert or utilize water hyacinth for biogas and liquid fertilizer. The objectives of the programs are approach the society by socializing about the benefits of water hyacinth convert to biogas and liquid fertilizer, to train skilled of people to build a biogas unit. The result of this programs makes a biogas unit MERCEDES (Mesophilic Reactor Anaerobic Digestion) which produces biogas and liquid fertilizer. The economic potential is obtained if all households apply them (equivalent with energy) about IDR 17.112 million per year, a liquid fertilizer about IDR 200.000 per household per day, the environmental potential reduction of water hyacinth growth about 6-15% per year, providing knowledge to the community to build a biogas unit and Mr. Musyafa has been utilize the biogas and fertilizer and have formed the structure of the organization to manage and develop the biogas unit for sustainability the program.